2021
DOI: 10.1007/s44154-021-00021-2
|View full text |Cite
|
Sign up to set email alerts
|

A secreted catalase contributes to Puccinia striiformis resistance to host-derived oxidative stress

Abstract: Plants can produce reactive oxygen species (ROS) to counteract pathogen invasion, and pathogens have also evolved corresponding ROS scavenging strategies to promote infection and pathogenicity. Catalases (CATs) have been found to play pivotal roles in detoxifying H2O2 formed by superoxide anion catalyzed by superoxide dismutases (SODs). However, few studies have addressed H2O2 removing during rust fungi infection of wheat. In this study, we cloned a CAT gene PsCAT1 from Puccinia striiformis f. sp. tritici (Pst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Deletion of each monofunctional catalase-encoding gene did not result in a phenotypic difference compared to the wild-type strain in F. graminearum ( Lee et al, 2018 ), while the transcript levels of all five catalases significantly increased upon H 2 O 2 treatment ( Lee et al, 2014 ), suggesting their redundant functions in the oxidative stress response. Among the identified typical catalases, PsCAT1 of P. striiformi , SsCAT1 and SsCAT2 of S. sclerotiorum , and CATB of Magnaporthe oryzae are required for fungal virulence ( Huang et al, 2021 ; Skamnioti et al, 2007 ; Yarden et al, 2014 ; Yuan et al, 2021b ). PsCAT1 and SsCAT2 are responsible for resistance to oxidative stress and it was confirmed that the deletion of both genes caused H 2 O 2 accumulation in host plant cells, indicating that two catalases are important for scavenging host-derived ROS.…”
Section: Antioxidant Systems and Their Role In Pathogenicitymentioning
confidence: 99%
“…Deletion of each monofunctional catalase-encoding gene did not result in a phenotypic difference compared to the wild-type strain in F. graminearum ( Lee et al, 2018 ), while the transcript levels of all five catalases significantly increased upon H 2 O 2 treatment ( Lee et al, 2014 ), suggesting their redundant functions in the oxidative stress response. Among the identified typical catalases, PsCAT1 of P. striiformi , SsCAT1 and SsCAT2 of S. sclerotiorum , and CATB of Magnaporthe oryzae are required for fungal virulence ( Huang et al, 2021 ; Skamnioti et al, 2007 ; Yarden et al, 2014 ; Yuan et al, 2021b ). PsCAT1 and SsCAT2 are responsible for resistance to oxidative stress and it was confirmed that the deletion of both genes caused H 2 O 2 accumulation in host plant cells, indicating that two catalases are important for scavenging host-derived ROS.…”
Section: Antioxidant Systems and Their Role In Pathogenicitymentioning
confidence: 99%